CONCEPTUAL METAPHOR AND METONYMY IN SPEECH ON THE PALESTINIAN CONFLICT - Artha, Artha Nur Restia Panji (Universitas Samudra, 2025)
Rishi Sunak’s speech On October 23 in response to the Israel-Palestina conflict has triggered moslem communities around the world. This is because the British Government has shown their support to Israel. This research aims to analyze the conceptual mapping of metaphors and metonymies found in the British PM’s speech as a style of conveying ideas in showing of their partiality. Data sources were obtained from the text of Rishi Sunak's speech on the official page of the United Kingdom. This research uses a qualitative approach with descriptive analysis. Lakoff and Johnson's cognitive semantic theory of metaphor and metonymy with map transferring is used as a framework in this study. The research findings show that there are about 13 conceptual metaphor data in Rishi Sunak's speech text with the most ontological metaphors found, with 8 data, compared to other metaphors, namely structural with 4 data, and orientation with 1 data. Ontological metaphors in this study mostly analogize abstract war issues with concrete concepts, while orientation relates to top-down spatial concepts and structural metaphors mostly describe the concept of war with other concepts. Meanwhile, the metonymy contained in the speech text largely represents the concepts of